Pengaruh Citra Merek terhadap Kepuasan dan Loyalitas Konsumen Restoran H. Masduki di Kota Pekalongan - Silfia, Anna; Sarma, Ma'mun (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2021)
Marketing competition conditions are getting tighter with a variety of products offered, commpanies or entrepreneurs are required to have high competitiveness, including the culinary business. H. Masduki restaurant is the one of family restaurants located in Pekalongan City. H. Masduki restaurant must be able to survive in the competition between similar restaurants in Pekalongan City in order to continue to exist. The objective of this research is to identify consumer characteristics, analyze the effect of brand image to customer satisfaction and loyalty, and analyze the effect of customer satisfaction to customer loyalty. The analytical tools used are descriptive analysis and Structural Equation Modelling (SEM) analysis with Partial Least Square (PLS) approach. The results of the research analysis is the brand image variable has a positive and significant effect on satisfaction and consumer loyalty and customer satisfaction has a significant positive effect on consumer loyalty.